2009
DOI: 10.2109/jcersj2.117.194
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of .BETA.-SiC/SiO2 core-shell nanowires by simple thermal evaporation

Abstract: Beta-SiC/SiO2 core-shell nanowires were obtained in a mullite boat after the reaction between silicon nanopowder and CH4 gas at 1623 K (1350°C), without adding metal catalysts from outside. The as-grown nanowires were characterized by X-ray diffractometry, scanning electron microscopy, transmission electron microscopy, scanning TEM, and infrared-ray spectroscopy.The results showed that the typical nanowires consisted of single crystalline β -phase SiC core of 50-70 nm in diameter and a uniform wrapping layer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…As mentioned before, 21) nanowires with cap were rarely observed in the products. The cap contained high concentration of Fe, which should come from the impurity in the raw powder.…”
Section: Formation Mechanism Of Nanowirementioning
confidence: 51%
See 4 more Smart Citations
“…As mentioned before, 21) nanowires with cap were rarely observed in the products. The cap contained high concentration of Fe, which should come from the impurity in the raw powder.…”
Section: Formation Mechanism Of Nanowirementioning
confidence: 51%
“…From these results, it can be confirmed that the as-grown nanowires should be SiC nanowires, as confirmed previously by EDX and FT-IR. 21) According to the above results, it was suggested that the Si raw powder with smaller size could produce larger amount of nanowires. One reason may be attributed for the difference in amount of oxygen content in the Si raw materials.…”
Section: Jcs-japanmentioning
confidence: 94%
See 3 more Smart Citations